Max Helsing and the beast of Bone Creek - Jobling, Curtis (Max Helsing: Monster Hunter, 2016)
"Max is hoping for some down time at a wilderness activity camp away from his monster-hunting day job. But it's not long before his idyllic getaway goes topsy-turvy and Max has to turn his sights towards the mythical Beast of Bone Creek: Sasquatch"--